GEOTERMAL METHOD IS SEISMOPROGNOSTIC RESEARCHES IN TRANSCARPATHIANS - Nazarevych, A.; Mykyta, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The futures of application of geothermal method in seismoprognostic researches in Transcarpathians are represented. The physics of fluid-hydrothermal processes as the physical basis of the method and also methodical-apparatus supply and some results of borehole geothermal researches are briefly considered.